2011
DOI: 10.47102/annals-acadmedsg.v40n11p493
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hearing Loss in Down Syndrome at First Year of Life

Abstract: Introduction: Infants with Down syndrome (DS) are at higher risk of hearing loss (HL). Normal hearing at one year of age plays an important part in language development. An audit was conducted to determine the impact of the newborn hearing screening program on the incidence, type and timing of diagnosis of HL during first year of life. Materials and Methods: Infants with DS were scheduled for Universal Newborn Hearing Screening (UNHS) within 4 weeks of life. If they passed, they had a high-risk screen at 3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our own studies, as well as those of other authors [7,9,18,31,32], have shown that not all objective tests can be performed in every case, but under good testing conditions (e.g. while asleep or performing quiet tasks), ABRs can usually be performed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our own studies, as well as those of other authors [7,9,18,31,32], have shown that not all objective tests can be performed in every case, but under good testing conditions (e.g. while asleep or performing quiet tasks), ABRs can usually be performed.…”
Section: Discussionmentioning
confidence: 61%
“…while asleep or performing quiet tasks), ABRs can usually be performed. In most cases, the diagnosis of a hearing disorder can be based on an ABR test result, with other tests such as tympanometry, wideband tympanometry (WBT), or otoacoustic emissions playing only a supporting role [7,9,18,30,32,33].…”
Section: Discussionmentioning
confidence: 99%